Electrochemical Characterization of Thin Film/Nanodots Electrodes of Silver and Gold for Biosensing CCRF-CEM Leukemia Cells - Farahdina, Ulya; Firdhaus, Miftakhul; Wulandari, Putri; Rubiyanto, Agus; Nasori, Nasori; Aziz, Ihwanul; Suprihatin, Hari; Jadid, Nurul; Ula, Rini Khamimatul (Applied Science and Engineering Progress, 2025)
This study presents a novel biosensor for detecting CCRF-CEM cells, derived from a T lymphoblastoid cell line, featuring intricate surface modification techniques. The fabrication process involves thin film deposition, electropolishing and dual anodization to create an anodic aluminum oxide template, followed by DC sputtering deposition to produce gold (Au) thin film/silver (Ag) nanodots and an Ag thin film/Au nanodots electrodes. Characterization using scanning electron microscopes (SEM), energy-dispersive X-ray spectroscopy (EDX), and X-ray diffraction (XRD) confirms electrode suitability for biosensing applications. Surface modification with aptamer Sgc8c and bovine serum albumin enables specific binding of CCRF-CEM cells while minimizing non-specific interactions. Electrochemical characterization via cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) reveals the biosensor’s sensitivity, selectivity, and reproducibility. The Au thin film/Ag nanodots electrode emerges as the most promising choice, exhibiting exceptional sensitivity (limit of detection (LOD) = 16 cell/10 mL), reproducibility, and selectivity for CCRF-CEM cells. This work highlights the importance of tailored surface development in biosensor design and lays the groundwork for highly sensitive and selective biosensors with potential applications in disease diagnosis and therapeutic monitoring.